KESIAPAN GURU MADRASAH DI KOTA SEMARANG DALAM MENGHADAPI PELAKSANAAN PPG - Amin Farikh (Kopertais Wilayah X Jawa Tengah, 2015)
AbstractProfessional Teacher Education (PTE/ PPG) can be regarded as a program to improve the competence of today’s most important teacher. This program is not solely the learning process of the teachers, but also as a starting point increase teachers’ welfare through the provision of teaching certi